Late Permian–Early Triassic environmental changes recorded by multi-isotope (Re-Os-N-Hg) data and trace metal distribution from the Hovea-3 section, Western Australia - Georgiev, S.V.; Stein, H.J.; Yang, G.; Hannah, J.L.; Böttcher, M.E.; Grice, Kliti; Holman, Alex; Turgeon, S.; Simonsen, S.; Cloquet, C. (ELSEVIER, 2020)
The temporal coincidence between the Late Permian mass extinction (LPME) and the emplacement of Siberian Trap basalts suggests a causal link between the two events. Here, we discuss stratigraphic changes of organic and inorganic (including isotopic) geochemical properties of marine sediments across the Permian–Triassic boundary (PTB) in the Hovea-3 core, Western Australia, a key PTB section in the southern Neo-Tethys ocean. These data are compared with published data from the Meishan section, southern China, and from the Opal Creek section in western Canada, providing a view of Tethys and Panthalassa changes at the PTB. Trace metal and N-isotopic data, together with organic matter properties suggest that anoxic conditions were established prior to the LPME, intensified close to the LPME, and continued with photic-zone euxinia into the Early Triassic. For the Hovea-3 section, Re-Os ages confirm Changhsingian (253.5 ± 1.4 Ma) deposition of the dated interval sampled immediately below the stratigraphic level characterized by major lithological and isotopic changes. Evaluation of Re-Os, N, and Hg elemental and isotopic data for Hovea-3 suggests that anoxic conditions in the latest Permian were generally unrelated to direct magmatic contributions. A major increase in the initial Os isotopic ratio of Lower Triassic shales suggest an ~8× increase in the Early Triassic continental runoff, based on moderately conservative assumptions for end-members contributing Os to the Permian–Triassic ocean. Comparison to other PTB sections confirms a global signal of increasing Re/Os ratios in the Late Permian, and major and long-lived changes in the isotopic composition of the post-extinction ocean. A distinct peak in Hg concentrations carrying a volcanic isotopic signature, also identified in other PTB sections, likely represents a major pulse of Siberian Trap volcanism. This Hg peak in the Hovea-3 section, however, is detected above the stratigraphic level containing multiple other widely recognized and more permanent geochemical changes. Therefore, direct volcanic inputs to the Permian–Triassic Ocean likely post-date the LPME in this Western Australian section.